Optimal adaptive communication protocols subject to dynamical and topological constraints - Almodaresi, Elham; Bajcinca, Naim (2016 Second International Conference on Event Based Control, Communication, and Signal Processing (EBCCSP), 2016)
We propose a systematic method to the design of adaptive communication protocols subject to a set of heterogeneous constraints, including continuous system dynamics, event-based communication and discrete topological constraints. To this end, we make use of a recent modeling formalism based on hybrid Petri nets, whose semantics is capable of capturing the information exchange between the nodes of a network system. The design problem is then given a hybrid dynamical formulation in form of a mixed-integer dynamical system. The proposed approach is directly applicable to the co-design problem of communication and control protocols.